Experimental Analysis of Recycled Concrete Microstructure Using Natural Aggregate Replacement Materials - Nur Ainun Hafifah; Muhammad Irsan; Muhammad Yusril Raynonto; Asri Mulya Setiawan (International Association of Lowland Technology, 2022)
Solid waste from construction residues can be used as a material for economic value recycled agregate concrete.The use of concrete waste as a substitute for coarse aggregate is expected to be able to overcome problems in environmental pollution.The addition of a superplasticizer to fresh concrete mixtures can increase the strength of the concrete produced with a small amount of water. This study aims to to determine the morphological composition of the recycled concrete microstructure by SEM testing and to determine the effect of natural aggregate substitute materials on the mechanical properties of recycled concrete. Variations of concrete waste used are 0%, 50% and 100%. The compressive strength and flexural strength test was carried out at 28 days of concrete. The test results show that the value of compressive strength of concrete is 43,52 Mpa at the variation of 100% concrete waste. Aluminum (Al2O3), Sulfur Trioxide (SO3), Phosphorus (P2O5) and Lime (CaO) are the most dominant elements in the hydration process of concrete.